62.5k views
2 votes
Anyone Willing to solve 33

Anyone Willing to solve 33-example-1
User Calebbrown
by
5.3k points

2 Answers

5 votes
The answer is P/2 - l = w
User Rahulmohan
by
5.6k points
5 votes

Start with


P = 2(l+w)

Expand the right hand side:


P = 2l+2w

Subtract 2l from both sides:


P-2l = 2w

Divide both sides by 2:


(P-2l)/(2)=w

And so we solved the equation for the width:


w = (P-2l)/(2)

User Mementum
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.